1994
DOI: 10.1038/370386a0
|View full text |Cite
|
Sign up to set email alerts
|

The ETS domain protein Pointed-P2 is a target of MAP kinase in the Sevenless signal transduction pathway

Abstract: The fate of the R7 photoreceptor cell in the developing eye of Drosophila is controlled by the Sevenless (Sev) receptor tyrosine kinase. Sev activates a highly conserved signal transduction cascade involving the proteins Ras1 and Raf and the Rolled/mitogen-activated protein (Rl/MAP) kinase. Here we show that the ETS domain protein encoded by the P2 transcript of the pointed (pnt) gene is a nuclear target of this signalling cascade which acts downstream of Rl/MAP kinase. The PntP2 protein is phosphorylated by R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
302
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(309 citation statements)
references
References 29 publications
4
302
0
Order By: Relevance
“…ETSdomain proteins have been implicated in regulating several key developmental processes. For example, Pnt regulates both eye (Brunner et al, 1994;O'Neill et al, 1994) and tracheal (Samakovlis et al, 1996) development in Drosophila whereas in mammals, Ets-1 (Bories et al, 1995;Muthusamy et al, 1995) and PU.1 (Scott et al, 1994;McKercher et al, 1996) have been implicated in regulating di erent aspects of haematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…ETSdomain proteins have been implicated in regulating several key developmental processes. For example, Pnt regulates both eye (Brunner et al, 1994;O'Neill et al, 1994) and tracheal (Samakovlis et al, 1996) development in Drosophila whereas in mammals, Ets-1 (Bories et al, 1995;Muthusamy et al, 1995) and PU.1 (Scott et al, 1994;McKercher et al, 1996) have been implicated in regulating di erent aspects of haematopoiesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, the two MAP kinases are highly related, sharing 82% (89%) sequence identity (similarity), exhibit comparable docking interactions, 40 and function in homologous signaling cascades. 9,18,20 Furthermore, Ets1 is also phosphorylated in vitro by ERK2 at the corresponding Thr38 and Ser41, and in vivo tests have confirmed that both these residues contribute to Ras-enhanced transactivation by ETS1. 4,17 Thus, the potential roles of Thr145 and Thr154 in the control of gene expression by Pointed-P2 remain to be evaluated.…”
Section: Map Kinase Docking By Pointed-p2mentioning
confidence: 88%
“…[18][19][20][21] However, the molecular mechanisms underlying this process have not been defined. By analogy to ETS1, 4,17 it is plausible that phosphorylation of Pointed-P2 leads to enhanced recruitment of Nejire, the Drosophila ortholog of the mammalian coactivator CBP.…”
Section: Map Kinase Docking By Pointed-p2mentioning
confidence: 99%
See 2 more Smart Citations